(untitled) (Global Journal of Advanced Engineering Technologies and Sciences, 2018)
This article focuses on geological-structural position and formation conditions of gold-containing deposits of Mekhmanian ore-magmatic system (OMS) according to tectonic position of deposits, material composition of ore-bearing and ore-hosting intrusive complexes, specifics of mineral composition, quantity and correlation of main and associated components. There is a new data allowing to estimate formation conditions and matter sources of OMS deposits. Productive mineralization has been determined which occurs by two stages: 1) quartzmolybdenite, quartz-chalcopyrite; 2) quartz-chalcosine-pyrite-chalcopyrite, sphalerite-galena-gold-rare-metal. At first stage concentrators of gold are pyrite and chalcopyrite, and its content is non-uniform, and at second stage gold-containing are represented by galena, sphalerite and also fahl ores and tellurides. We distinguish three goldbearing associations according to mineral composition of ores, they are: quartz-molybdenite-chalcopyrite, quartzpyrite-chalcopyrite and quartz-galena-sphalerite.